Pengembangan Media Pembelajaran Matematika Berbasis Android Menggunakan I-Spring Suite Pada Materi Turunan Fungsi Aljabar - Rihi, Michael Marselino; Nenohai, Juliana M.H; Rimo, Imelda Hendriani Eku (Universitas Dr. Soetomo, 2024)
Abstract One form of technology utilization in the world of education, especially in the learning process, is the development of learning media based on android applications. In the mathematics learning activities that occur at SMA Negeri 4 Kupang, especially in grade XI, educators use PPT and teaching materials as tools in learning, but the media is less interactive because it is still limited to ordinary PPT, so that the lack of enthusiasm of students in the learning process has an impact on the low interest and learning outcomes of the students themselves. This is also one of the factors that learning in the classroom is not carried out properly due to the inappropriate use of learning media. Therefore, the purpose of this research is to be able to create an android-based mathematics learning media with the help of the I-Spring suite on the derivative material of the algebra function of class XI at SMA Negeri 4 Kupang which is valid, practical, and effective which is then named the Nubar Application (turuNUnan aljaBAR). Research and development (R&D) is a method used in this study by applying the ADDIE development model, namely analysis, design, development, implementation and evaluation. In this study, data was obtained through interviews, questionnaires and learning outcome tests. The data analysis techniques used are qualitative data analysis and quantitative data analysis. From the research that has been carried out, it shows that the Nubar Application that has been developed has entered the eligibility criteria for learning media, namely valid, practical and effective. Keywords: Algebra Function Derivation; Android-Based Learning Media; Development; I-Spring Suite. Abstrak Salah satu bentuk pemanfaatan teknologi dalam dunia pendidikan terkhususnya dalam proses pembelajaran yaitu, pengembangan media pembelajaran berbasis aplikasi android. Dalam kegiatan pembelajaran matematika yang terjadi di SMA Negeri 4 Kupang khususnya di kelas XI pendidik menggunakan PPT dan bahan ajar sebagai alat bantu dalam pembelajaran, namun media tersebut kurang interaktif dikarenakan masih terbatas pada PPT biasa, sehingga kurangnya antusias peserta didik dalam proses pembelajaran yang berdampak pada rendahnya minat serta hasil belajar peserta didik itu sendiri. Hal ini juga menjadi salah satu faktor pembelajaran di kelas tidak terlaksana dengan baik dikarenakan Penggunaan media pembelajaran yang kurang tepat. Oleh sebab itu, tujuan dari riset ini ialah dapat menciptakan sebuah media pembelajaran matematika yang berbasis android dengan bantuan I-Spring suite pada materi turunan fungsi aljabar kelas XI di SMA Negeri 4 Kupang yang valid, praktis, dan efektif yang kemudian diberi nama Aplikasi Nubar (turuNUnan aljaBAR). Research and development (R&D) merupakan metode yang diapakai dalam penelitian ini dengan menerapkan model pengembangan ADDIE, yaitu analisis, desain, pengembangan, implementasi dan evaluasi. Dalam penelitian ini, data diperoleh melalui wawancara, angket dan tes hasil belajar. Adapun teknik analisis data yang dipakai yaitu analisis data kualitatif dan analisis data kuantitatif. Dari penelitian yang telah dilaksanakan, menunjukan bahwa Aplikasi Nubar yang telah dikembangkan telah masuk kriteria kelayakan media pembelajaran yaitu valid, praktis dan efektif. Kata Kunci: I-Spring Suite; Media Pembelajaran berbasis Android; Pengembangan; Turunan Fungsi Aljabar